PLIKASI TEKNOLOGI KNOCK DOWN UNTUK PEMBANGUNAN RUMAH DAN SEKOLAH TERBUKA KORBAN BENCANA TSUNAMI DI ACEH DAN SUMATERA UTARA - Sugestiyadi, Bambang (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
In  the  framework   of  realization   of  Tri  Darma   Perguruan   Tinggi program,    Technique    Faculty    of   Yogyakarta    State   University    (YSU) contributes  idea  for  Tsunami   disaster  victims  in Aceh  and North  Sumatra that  was   happened    on   26th   December    2004.   The   contribution    of   the Technique   Faculty   of  Yogyakarta    State  University   (YSU)   for  Tsunami disaster  in  Aceh  and  North   Sumatra   is  given  in  the  form  of  a  Planning Concept of Housing  and Open Schools.The  planning   for  Houses  and  opens  Schools  for  Tsunami   disastervictims  in Aceh  and North  Sumatra  is consideres  with  many  aspects,  i.e.  : (1) Functional  aspect,  (2) Social  culture  aspect,  (3) Construction   aspect  (in relation   with   nature   condition    and   disaster),   (4)  Technical   aspect,   (5) Economical  aspect,  and (6) Field implementation   aspect.The result  of the planning  for Housing  and Open Schools  is suitablewith  geographical   condition   in  Aceh  and  its  emergency   condition   that  is happening  there,  and North  Sumatra  after Tsunami  are as follows:  (a) In the form of house  on stilts,  (b)  'Knock   Down'   construction   system,  (c) Using local wood, and (d) House  construction  that can put up with earthquake.Key words: Housing  and Open Schools, After  Tsunami